2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6696539
|View full text |Cite
|
Sign up to set email alerts
|

Spine dynamics as a computational resource in spine-driven quadruped locomotion

Abstract: Recent results suggest that compliance and nonlinearity in physical bodies of soft robots may not be disadvantageous properties with respect to control, but rather of advantage. In the context of morphological computation one could see such complex structures as potential computational resources. In this study, we implement and exploit this view point in a spine-driven quadruped robot called Kitty by using its flexible spine as a computational resource. The spine is an actuated multi-joint structure consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…The separation property means that the input signals that should be distinguished are mapped to different physical states. The dynamics of soft materials, (3)(4)(5)(6) fluids, (7,8) mass-spring systems, (14,15) electronic circuits, (16) optical circuits, (17) memristors, (18) spintronic systems, (19) quantum systems, (20) and so forth have been exploited as computational resources for physical reservoir computing, and it has been experimentally shown that the systems have computational ability in benchmark tasks. (12,13) (b) physical reservoir computing using a mass-spring system, (14) and (c) proposed physical reservoir computing using a pneumatic pipeline system.…”
Section: Concept Of Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation property means that the input signals that should be distinguished are mapped to different physical states. The dynamics of soft materials, (3)(4)(5)(6) fluids, (7,8) mass-spring systems, (14,15) electronic circuits, (16) optical circuits, (17) memristors, (18) spintronic systems, (19) quantum systems, (20) and so forth have been exploited as computational resources for physical reservoir computing, and it has been experimentally shown that the systems have computational ability in benchmark tasks. (12,13) (b) physical reservoir computing using a mass-spring system, (14) and (c) proposed physical reservoir computing using a pneumatic pipeline system.…”
Section: Concept Of Proposed Methodsmentioning
confidence: 99%
“…In the control of some robots, locomotion was controlled by using signals from sensors embedded in the soft part of the body. (3,4) It has been shown that a soft arm resembling an octopus arm can be exploited for some computational tasks, such as a parity check. (5,6) These methods, however, use some movements of the robot itself for computation and require a specially designed body morphology [e.g., tensegrity structure (4) ] to be used in combination with the robot's primarily required motion (e.g., locomotion).…”
Section: Introductionmentioning
confidence: 99%
“…5 The developed model has possible applications in fields such as search and rescue operations, military sector, mining, construction, and robotics for autonomous exploration and monitoring. 6 Additionally, the results could help researchers understand better the dynamic behavior of legged robots, contributing to future designs' improvement.…”
Section: Introduction 11 Motivationmentioning
confidence: 99%
“…The idea has a wide number of applications within its scope. MC is sometimes referred to as the possibility of using the complex nonlinear dynamics of a deformable body to serve as a computational resource in control tasks Nakajima et al (2014Nakajima et al ( , 2015; Hauser et al (2018), with a particular focus on soft manipulators control Nakajima et al (2013); Eder et al (2017) and locomotion Zhao et al (2013). A different branch of MC can be found in the field of robot locomotion, where the interaction with a complex and nonstructured environment is not handled by means of complex controllers, but by harnessing the intrinsic properties of the materials used in construction Auerbach and Bongard (2017); Calisti et al (2017).…”
Section: Introductionmentioning
confidence: 99%